IMPLEMENTATION OF PROBLEM BASED LEARNING AND TEACHING AT THE RIGHT LEVEL (TARL) APPROACH COMBINED WITH GAMES FACTS ABOUT ME AS AN EFFORT TO IMPROVE STUDENTS' HIGHER LEVEL THINKING SKILLS - Roidah Affifah, Jihan; Zubaidah, Siti; Melati, Rika (Universitas Negeri Malang, 2023)
The implementation of the Merdeka Curriculum necessitates the development of high-level thinking skills, a crucial aspect of 21st-century competencies. This research aims to enhance students' higher-order thinking skills by applying the Problem-Based Learning (PBL) model in conjunction with the Teaching at the Right Level (TaRL) approach and educational games. The study focused on seventh-grade students at SMP Negeri 16 Malang. Employing a qualitative research design, the case study method was utilized to gain in-depth insights. Data were collected through observations conducted by the researchers and several observers during the learning activities. The findings from the observations indicated a significant improvement in students' higher-order thinking skills following the implementation of the PBL model and TaRL approach. Additionally, integrating educational games proved to be an effective strategy for engaging students and facilitating a deeper understanding of complex concepts. This research underscores the potential of innovative teaching methods to foster critical thinking and enhance educational outcomes in contemporary learning environments.